ส่วนประสมการตลาดที่มีผลต่อลูกค้าในการซื้อบ้าน โครงการบ้านจัดสรรมาลาดาโฮม แอนด์ รีสอร์ท จังหวัดเชียงใหม่ - อธิภัทร เดชอานันท์ภร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to explore marketing mix affecting customers in purchasing houses from Malada Home and Resort Project, Chiang Mai province. The data were compiled from 130 questionnaires distributed to customers who bought and lived in Malada Home and Resort Project, Chiang Mai province. The given data were then analyzed by using descriptive statistics consisted of a frequency, a percentage, and a mean. The research results were summarized as follows. From the study, it was found that most customers were married female aging between 31 to 40 years old. Most of them were business women graduated with Bachelor’s Degrees. Their average family income per month was 40,001 to 60,000 Baht. Most of them were born in Chiang Mai Province. Their family members were 3 to 4 people. Most of them had purchased houses from other housing development projects before purchasing from Malada Home and Resort Project, Chiang Mai Province. They had considered other 3 to 4 housing development projects before they decided to purchase houses from Malada Home and Resort Project, Chiang Mai Province. It had taken them 3 to 4 weeks to make a decision after they had started gathering information about Malada Home and Resort Project, Chiang Mai Province. Most of them purchased Townhomes ranging from 20 to 50 square wah. The price of their houses (at the time of purchase) was from 2,900,001 to 3,900,000 Baht. Most of them paid for their houses with a loan. The main reason for their decision to purchase houses from Malada Home and Resort Project, Chiang Mai Province, was because the house plans were beautiful. Billboards were the main source of information regarding Malada Home and Resort Project, Chiang Mai Province. The people who had the most influence over their decisions to purchase houses from Malada Home and Resort Project, Chiang Mai Province were their spouses and children. Regarding the marketing mix factors affecting the customers in purchasing houses from Malada Home and Resort Project, Chiang Mai Province, it was found that the marketing mix factors with the high significant levels were Product, Promotion, and Place; whereas the marketing mix factors with the medium significant level was Price, respectively. The 10 sub-factors of the marketing mix factor affecting the customers in purchasing from Malada Home and Resort Project, Chiang Mai Province with the highest average were as followed. Several multimedia were extensively used in advertising such as brochures or pamphlets, via internet or radio. The houses were unique and modern. The sizes of the lands and the houses were suitable and met the needs of the customers. There was advertising on big billboards at crossroads such as Ton Kwen Crossroad (Nong Khwai Municipality) and Royal Flora Ratchapruek Crossroad. The plans of the houses were beautiful. The purchasing process was simple and uncomplicated, with prompt after-sale-service. The sales office of the housing project was close to the community such as temples, schools, banks, etc. There was advertising via several multimedia such as Home Buyer’s Guide Chiang Mai Magazine. There were house plans available for considering before purchasing. And the prices of the houses were cheaper than those of other housing projects nearby, respectively.